Identifikasi Kemampuan Berpikir Kritis Matematis Mahasiswa Berkemampuan Pemecahan Masalah Level Rendah dalam Pembelajaran Kalkulus Integral Berbasis Problem Based Learning - Nursyahidah, Farida; Albab, Irkham Ulil (Universitas Hamzanwadi, 2018)
The aim of this research is to describe crithical thinking ability of the students with low problem solving ability in solving problem in Riemann Integral based on the criteria of critical thinking in problem based learning. This is qualitative research with the subject is the students in the class IIE of year 2016/2017 mathematics education departement of FPMIPATI UPGRIS who join the the Calculus Integral course. The data collection used is test and interview. Based on the result of this research can be known that profile of critical thinking ability with the low level of problem solving ability was can do basic clarification, can not do bases for a decision, can not do inference, can not do advance clarification, and can not do supposition and integration.